The Environmental Assessment Process and Public Participation in Québec: Concrete Elements for Sustainable Development - Renaud, Pierre (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1996)
In southern Québec, projects having major environmental impact are subjected to the environmental assessment process which provides a period of information and consultation. During this period, any citizens, groups or municipalities can ask the Minister of the Environment and Wildlife to conduct, through the BAPE, a public inquiry on the project. This environmental impact assessment process, in place since 1978, was a precursor of sustainable development. The present paper is a presentation of the practical working of the environmental process at the government level.